(untitled) (Research, Society and Development, 2021)
Conduct a literature review to analyze the challenges faced by nursing professionals in order to carry out hospital hygiene, addressing a multifaceted perception of the trajectory related to the problem. It is an exploratory research of the literature review type, being an essential method in the elaboration of a scientific work. It was divided into 6 stages, with the creation of the theme and guiding question, definition of inclusion and exclusion criteria, identification of studies on scientific bases, evaluation of selected studies and critical analysis, analysis and categorization of studies and evaluation and interpretation of results. The total number of studies included was 26 articles, estimating the highest percentage of productions on the subject accounted for 30.77% in 2016, followed by 26.92% in 2017, followed by 15.38%, 11, 54% and 19.23% found simultaneously in the years 2018, 2019 and 2020. The analyzed articles converge in the sense that the nursing team is essential for the success of the maintenance of hygiene in the hospital sectors, being such a fundamental act for the maintenance or / and decreased damage to the patient’s health. We realize, therefore, the importance of historical knowledge to understand the current scenario of the country, since, from the environmental and health ideologies defended by activists of the 19th century.